Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 11 - Cumulative Review - Page 670: 39


$(2,\sqrt 2)$

Work Step by Step

$y= \sqrt x$ Equation $(1)$ $x^{2}+y^{2}= 6$ Equation $(2)$ Substitute $y= \sqrt x$ in Equation $(2)$ we get, $x^{2}+y^{2}= 6$ $x^{2}+(\sqrt x)^{2}= 6$ $x^{2}+x= 6$ $x^{2}+x- 6=0$ By factoring, $(x-2)(x+3)=0$ $x=2$ or $x=-3$ Substitute $ x$ values in Equation $(1)$ to get $y$, Let $x=2$ $y= \sqrt 2$ Let $x=-3$ $y= \sqrt (-3)$ is not a real number. $(2,\sqrt 2)$ satisfies both equations. So, $(2,\sqrt 2)$ is the only solution.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.